New analyses of Antarctic carbonaceous chondrites - Moore, Carleton B.; Cronin, John R.; Pizzarello, Sandra; Ma, Maw-Suen; Schmitt, Roman A. (1981)
P(論文) New analyses have been made on the Antarctic carbonaceous chondrites ALHA77306 and ALHA77307. Only traces of amino acids have been detected in ALHA77307. Non-protein amino acids were not detected. Inorganic analyses using INAA techniques showed no significant differences between interior and exterior pieces of ALHA77306. ALHA77306 is a C2 chondrite and ALHA77307 a C3V chondrite. departmental bulletin paper